The effects of local endometrial injury made by hysteroscopy on in vitro fertilization outcome - Mitić, Dejan S; Bašić, Marin; Petrić, Aleksandra; Stamenović, Snežana (Vojnosanitetski pregled, 2020)
Bacngraund/Aim. Regardless of embryos quality, an appropriate endometrial thickness and a successful embryo transfer (ET), implantation remains a difficulty for a favorable outcome of an in vitro fertilization (IVF). Numerous studies with the aim of increasing implantation rate and pregnancy rate suggest local endometrial injury (LEI) prior to the IVF procedure. Hysteroscopy is a method becoming more widely used both with patients after a failed IVF cycle and with patients before the first IVF, considering the large incidence of uterus cavum pathological states which have a negative impact on the favorable outcome. However, there is still no consensus reached over LEI, the way and time of its performing or its impact. The aim of this research was to determine the effect of hysteroscopically made local endometrial lesion on the IVF procedure outcome, both in the first and in the next IVF cycle and also to examine if the new method of LEI provoking using bipolare electrode has a favorable impact on post IVF pregnancy success. Methods. Total of 81 patients had hysteroscopy performed 30–50 days prior to IVF, 40 of which had LEI made during hysteroscopy (the LEI group) using bipolar electrode in a way not described in any available literature. Remaning histeroscopically treated patients (n = 41) had no LEI (the non-LEI group). The control group included 151 patient who had IVF performed with no prior hysteroscopy and LEI.  Results. The rate of clinical pregnancies after LEI was statistically more significant in comparison to the control group (52.50% vs 34.44%, p < 0.05) and it meant 2.1 time bigger chance to conceive (OR=2.10; 95% CI: 1.04 – 4.26; p < 0.05). We noticed differences in the implantation rate between the LEI group and the non-LEI group on one side and the control group on the other, in favor of the two groups subjected to hysteroscopy (23.89%, 25.47% vs 18.18%, respectively), but they were not of any statistical significance. Not significantly higher rate of pregnancy was present, after the first and the next IVF, both in the LEI and the non-LEI group when compared to the control one. Conclusion. New method of LEI provoking by bipolar electrode in the process of hysteroscopy is a simple and safe method allowing higher rate of clinical pregnancies and doubling the probabilty of the positive IVF outcome.
Keywords: infertility; fertilization in vitro; hysteroscopy; iatrogenic disease; uterus; wounds and injuries; pregnancy outcome